IMPLEMENTASI P5 DALAM MEMBENTUK KARAKTER BUDAYA PESERTA DIDIK DI SD NEGERI 227 PALEMBANG - MARSELA, FAIDAH; MISDALINA, MISDALINA; ABDULLAH, SEPTEIYAWAN (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2024)
Strengthening the Pancasila student profile is a cross-disciplinary learning to observe environmental problems and find solutions to strengthen competencies in the Pancasila student profile. The implementation of the independent curriculum in P5 activities is very important to promote local culture in forming cultural character in students. Efforts to develop students' cultural character include developing and implementing a good school culture in front of students. The purpose of this study was to determine the form of P5 implementation in forming the cultural character of students at SD Negeri 227 Palembang, to determine the efforts of teachers and the results in forming cultural character in students at SD Negeri 227 Palembang, to determine what are the supporting and inhibiting factors in implementing P5 to form the cultural character of students at SD Negeri 227 Palembang. Data collection techniques in this study used observation, interview and documentation techniques. The form of P5 implementation is by performing traditional dances, coloring pictures of traditional dances, participating in cultural competitions and also making short stories about traditional dances, while the efforts made by teachers introduce the history of traditional dances. And the supporting factors in this P5 activity are that the school provides facilities and budget, the enthusiasm of teachers and school residents, students are invited to watch traditional dance videos, while the obstacles to P5 activities are limited time in preparing the P5 schedule and differences in student characteristics. ABSTRAKPenguatan profil pelajar Pancasila merupakan pembelajaran lintas disiplin ilmu untuk mengamati permasalahan lingkungan sekitar dan mencari solusi untuk menguatkan kompetensi dalam profil pelajar Pancasila. Penerapan kurikulum merdeka tersebut dalam kegiatan P5 sangatlah penting untuk mengangkat budaya lokal dalam membentuk karakter budaya pada siswa. Upaya dalam mengembangkan karakter budaya siswa salah satunya dengan mengembangkan serta menerapkan budaya sekolah yang baik di depan siswa. Tujuan penelitian ini untuk mengetahui bagaimana bentuk implementasi P5 dalam membentuk karakter budaya peserta didik di SD Negeri 227 Palembang, untuk mengetahui bagaimana upaya guru dan hasil dalam membentuk karakter budaya pada peserta didik di SD Negeri 227 Palembang, untuk mengetahui apa saja faktor pendukung dan penghambat dalam mengimplementasi P5 untuk membentuk karakter budaya peserta didik di SD Negeri 227 Palembang. Teknik pengumpulan data dalam penelitian ini mengunkan teknik observasi, wawancara dan dokumentasi. Bentuk implementasi P5 adalah dengan melakukan tarian tradidional, mewarnai gambar tarian tradisional, mengikuti lomba kebudayaan dan juga membuat cerpen tentang tarian tradisional, sedangkan upaya yang di lakukan guru memperkenalkan sejarah tarian tradisional. Dan faktor pendukung dalam kegiatan P5 ini sekolah menyediakan fasilitas dan anggaran, antusias guru dan warga sekolah, siswa di ajak meneonton vidio tarian tradisional sedangkan penghambat kegiatan P5 keterbatasan waktu dalam menyusun jadwal P5 dan perbedaan kerasteristik siswa.